EZH1/2 plays critical roles in oocyte meiosis prophase I in mice - Ting Jiang; Chengxiu Zhang; Xinjing Cao; Yingpu Tian; Han Cai; Shuangbo Kong; Jinhua Lu; Haibin Wang; Zhongxian Lu (Biological Research)
Abstract Backgroud abnormalities or defects in oocyte meiosis can result in decreased oocyte quality, reduced ovarian reserve, and female diseases. However, the mechanisms of oocyte meiosis remain largely unknown, especially epigenetic regulation. Here, we explored the role of EZH1/2 (histone methyltransferase of H3K27) in mouse oocyte meiosis by inhibiting its activity and deleting its gene. Results with embryonic ovary cultured in vitro, EZH1/2 was demonstrated to be essential for oocyte development during meiosis prophase I in mice. Activity inhibition or gene knockout of EZH1/2 resulted in cell apoptosis and a reduction in oocyte numbers within embryonic ovaries. By observing the expression of some meiotic marker protein (γ-H2AX, diplotene stage marker MSY2 and synapsis complex protein SCP1), we found that function deficiency of EZH1/2 resulted in failure of DNA double-strand breaks (DSBs) repair and break of meiotic progression in fetal mouse ovaries. Moreover, Ezh1/2 deficiency led to the suppression of ATM (Ataxia Telangiectasia Mutated kinase) phosphorylation and a decrease in the expression of key DNA repair proteins Hormad1, Mre11, Rad50, and Nbs1 in fetal mouse ovaries, underscoring the enzyme’s pivotal role in initiating DNA repair. RNA-seq analysis revealed that Ezh1/2-deletion induced abnormal expression of multiple genes involved into several function of oocyte development in embryonic ovaries. Knockout of Ezh1/2 in ovaries also affected the levels of H3K9me3 and H4K20me2, as well as the expression of their target genes L3mbtl4 and Fbxo44. Conclusions our study demonstrated that EZH1/2 plays a role in the DSBs repair in oocyte meiosis prophase I via multiple mechanisms and offers new insights into the physiological regulatory role of histone modification in fetal oocyte guardianship and female fertility.